Helicobacter pylori and Cardiovascular Diseases - Ju Yup Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Since its discovery, Helicobacter pylori (H. pylori) has played a central role in the pathogenesis of gastroduodenal diseases. Additionally, there have been many studies that demonstrated the role of H. pylori infection in extragastric diseases. Many research studies have confirmed an indirect association between the prevalence of H. pylori infection and the occurrence of cardiovascular diseases (CVDs); however, the results are still conflicting. Most studies found that the involvement of H. pylori in this process was related to the chronic inflammation. This inflammation may facilitate the development of CVD-related atherosclerotic pathologies such as endothelial damage and chronic activation of coagulation cascade, etc. Furthermore, H. pylori infection is known to be associated with other vascular diseases such as cerebrovascular diseases and cardiac arrhythmias, especially atrial fibrillation. This review summarized the literature on the association of cardiovascular manifestations and H. pylori infection and provided information about the pathogenesis of this association.